2007
DOI: 10.4049/jimmunol.179.8.5211
|View full text |Cite
|
Sign up to set email alerts
|

A Link between PDL1 and T Regulatory Cells in Fetomaternal Tolerance

Abstract: Acceptance of the fetus expressing allogeneic paternal Ags by the mother is a physiologic model of transplantation tolerance. Various mechanisms contribute to fetal evasion from immune attack by maternal leukocytes. We have recently demonstrated that the inhibitory costimulatory molecule PDL1 plays a critical role in fetomaternal tolerance in that PDL1 blockade or deficiency resulted in decreased allogeneic fetal survival rates. CD4+CD25+ T regulatory cells (Tregs) have also been demonstrated to play an import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
121
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(135 citation statements)
references
References 51 publications
12
121
2
Order By: Relevance
“…These gene markers were selected for the following reasons: CD3 as a control to follow potential changes in T cell composition at transcriptional level, CD69 as Haider et al (15) showed that nonresponders express higher transcription levels of CD69 in pretreatment PBMCs, Foxp3 to indirectly study changes in regulatory T cell frequencies, PD-L1 to asses differences in gene expression of negatively regulating costimulatory molecules (23)(24)(25)(26)(27)(28), and TOAG-1 (Acc. No: BE115945) and RHAMM as they have been recently described to be differentially expressed in the periphery during induction and maintenance of immunological tolerance in allogeneic kidney graft recipients (29).…”
Section: Discussionmentioning
confidence: 99%
“…These gene markers were selected for the following reasons: CD3 as a control to follow potential changes in T cell composition at transcriptional level, CD69 as Haider et al (15) showed that nonresponders express higher transcription levels of CD69 in pretreatment PBMCs, Foxp3 to indirectly study changes in regulatory T cell frequencies, PD-L1 to asses differences in gene expression of negatively regulating costimulatory molecules (23)(24)(25)(26)(27)(28), and TOAG-1 (Acc. No: BE115945) and RHAMM as they have been recently described to be differentially expressed in the periphery during induction and maintenance of immunological tolerance in allogeneic kidney graft recipients (29).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, embryonic cells were shown to be immunogenic, but their inherent immune privilege property promote the induction of tolerance by reducing the number of professional antigen presenting cells and increased expression of soluble factors that favor the generation of regulatory T cells [27]. In addition, cord blood stem cells have been shown to be immune privileged through the expression of B7-H1 (a negative co-stimulatory molecule that inhibit T-cell activation) and it is ability to induce regulatory T-cells [28]. Interestingly, reprogramming adult cells by merely introduction of four transcriptional factors to generate pluripotent stem cells (iPSC) did not have such immune privilege [29], suggesting the presence of other genetic differences between embryonic stem cells and iPSCs.…”
Section: Immunogenicity Of Embryonic Stem Cellsmentioning
confidence: 99%
“…In continuation of their previous observations that abrogation of tolerance at the FMI by PDL1 blockade is mediated through the maternal T cells, Habicht et al provided further evidence that PDL1 blockade results in functionally deficient Tregs. [46] The above observations suggest an indirect effect of PDL1 blockade on alloreactive maternal T cells which is mediated through Tregs that are rendered inefficient and unable to regulate the tolerance mechanism at the FMI. Blockade of PDL1 also results in excessive inflammation, observed by high IFN-Îł production, creating a pro-inflammatory environment conducive to Th1/Th17 effector T cell induction and proliferation.…”
Section: Pd1/pdl1 Pathway and Feto-maternal Tolerancementioning
confidence: 99%
“…The plasticity of the Th cell population, specifically conversion between the T regulatory and the Th17 phenotype, may explain the regulation of T cell tolerance at the FMI. The PD1/PDL1 pathway plays an important role in this mix, as it directly affects the suppressive properties of the Treg population [46] as well as abrogates the protective effects of Treg treatment. [42] Blockade of PD1/ PDL1 pathway also prevents the conversion of naĂŻve Th cells to a Treg phenotype, [79] thereby creating a bias toward an inflammatory environment that is conducive for the survival and expansion of both Th1 and Th17 types of cell populations.…”
Section: Pd1/pdl1 Pathway and Feto-maternal Tolerancementioning
confidence: 99%
See 1 more Smart Citation